Preparation method and application of biomass derived carbon / bimetallic phosphide

By using biomass -derived carbon/dual -metal phosphones composite materials in the positive electrode material of lithium sulfur batteries, the problem of polyohydride shuttle in lithium sulfur batteries has significantly improved the cycle performance and magnification performance of the battery.

CN119349520AActive Publication Date: 2025-01-24SOUTHWEAT UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411486525.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

In practical applications, lithium-sulfur batteries face problems such as low sulfur conductivity, large sulfur volume expansion during charging and discharge, and shuttle effect of soluble polysulfides, resulting in a decrease in Coulomb efficiency, sulfur utilization and cycling stability.

Method used

The composite material of biomass -derived carbon/dual metal phosphorus is used as a lithium sulfur battery positive electrode material. It uses potassium hydroxide alkali and high -temperature carbonized legal system for porous carbon materials, and synthesizes FBC/COMOP through water thermal heat and gas phosphorusization method. Composite materials to realize physical packaging and chemical regulation of polypsy.

Benefits of technology

Significantly improve the discharge specific capacity, cycle performance and rate performance of lithium-sulfur batteries, alleviate the diffusion and shuttle effects of polysulfides, and improve the stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349520A_ABST
    Figure CN119349520A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of biomass-derived carbon / bimetallic phosphide and application of the biomass-derived carbon / bimetallic phosphide in a lithium-sulfur battery positive electrode material. The preparation method comprises the following steps: firstly, preparing a biomass-derived carbon material (FBC) by taking a ficus pumila interlayer as a raw material by adopting a KOH alkalization method and a tubular furnace high-temperature carbonization method; preparing an FBC / CoMoO4 material by taking ammonium molybdate tetrahydrate and cobalt nitrate hexahydrate as raw materials through a hydrothermal method, preparing an FBC / CoMoP composite material by taking sodium hypophosphite monohydrate as a phosphorus source through a gas phase phosphorization method, and finally melting the FBC / CoMoP composite material with sublimed sulfur powder to prepare a positive electrode material applied to the lithium-sulfur battery. The biomass carbon material can form a three-dimensional conductive carbon skeleton through activation, and efficient transmission of electrons / ions is promoted. Meanwhile, the unique electronic property of the metal phosphide can adjust the electronic structure of the lithium polysulfide on the surface, so that diffusion and shuttling of the polysulfide are relieved. The combination of the bimetallic phosphide and the biomass porous carbon material has a unique effect in the aspect of accelerating the conversion of the dynamics of the lithium-sulfur battery, and shows a synergistic effect of '1 + 1gt; 2'.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur battery materials, and in particular to a method for preparing a biomass-derived carbon / bimetallic phosphide and application of the biomass-derived carbon / bimetallic phosphide prepared by the preparation method in a lithium-sulfur battery positive electrode material. Background Art

[0002] Lithium-sulfur batteries are one of the new generation of electrochemical energy storage systems due to their environmental friendliness, low cost, high theoretical specific capacity (1675mAh / g) and energy density (2600Wh / kg). However, lithium-sulfur batteries face a series of problems and challenges in practical applications, such as low sulfur conductivity, large volume expansion of sulfur during charge and discharge, and soluble polysulfides (Li2S n , 4≤n≤8) shuttle effect, etc. These problems have led to the decline of Coulombic efficiency, sulfur utilization and cycle stability of lithium-sulfur batteries, hindering their further development. In order to solve these problems, researchers have invested a lot of work to deal with these problems to improve the performance of lithium-sulfur batteries.

[0003] Biomass raw materials are used to prepare porous carbon because they are abundant in nature, easy to obtain, low-cost, and have original and unique microstructures. The prepared porous carbon has the characteristics of adjustable pore structure, large specific surface area, and large adsorption capacity, which helps to enhance the specific capacity and cycle stability of the battery. Biomass-derived porous carbon contains some macropores to achieve high sulfur loading, uniform sulfur distribution, provide fast ion transport channels, and sufficient space to buffer volume changes, while the geometric restrictions and strong physical adsorption of lithium polysulfides (LiPSs) require a large number of micropores to provide. Transition bimetallic phosphides have excellent electrical conductivity and excellent electrocatalytic performance. Their phosphide groups have lone pairs of electrons in 3p orbitals and 3d orbitals, which can improve electronic conductivity. The appropriate content of phosphide groups is of great significance to the conductivity of transition metal phosphides. The electronic structure of polysulfides can be adjusted on the surface through the electronic properties of transition metal phosphides, thereby accelerating the reaction kinetics.

[0004] In view of the above shortcomings, although relevant studies have shown that the "shuttle effect" can be suppressed by carbon materials or metal phosphide strategies, the combination of non-polar porous carbon materials and polysulfides is weak and cannot effectively adsorb and catalyze the conversion of polysulfides. Therefore, an ideal host material should have physical barriers and chemical adsorption to prevent lithium polysulfide from diffusing into the electrolyte. Biomass carbon materials can form a three-dimensional conductive carbon skeleton through activation to promote efficient electron / ion transmission. By combining biomass porous carbon materials with transition metal phosphides, lithium polysulfide can be physically adsorbed and chemically regulated. At the same time, the unique electronic properties of transition bimetallic phosphides can regulate the electronic structure of lithium polysulfide on the surface to alleviate the diffusion and shuttling of polysulfides. The combination of three-dimensional porous carbon materials and transition metal phosphides realizes the synergistic adsorption and catalytic conversion of LiPSs. Summary of the invention

[0005] In order to solve the problems existing in the above-mentioned lithium-sulfur batteries, the present invention provides a method for preparing biomass-derived carbon / bimetallic phosphide and its application in the positive electrode material of lithium-sulfur batteries. The composite material is applied in lithium-sulfur batteries, and the porous structure can physically encapsulate polysulfides. A large number of highly catalytically active sites can improve the conversion reaction kinetics of polysulfides, which can significantly improve the discharge specific capacity, cycle performance and rate performance of lithium-sulfur batteries.

[0006] In view of the challenges faced by the field of lithium-sulfur batteries, the present invention provides a method for preparing FBC / CoMoP as a positive electrode material for lithium-sulfur batteries. The method adopts potassium hydroxide alkalization method and tubular furnace high-temperature carbonization method, and uses the middle layer of Ficus pumila as raw material to prepare biomass porous carbon material. Then, ammonium molybdate tetrahydrate (H 24 Mo7N6O 24 ·4H2O) and hexahydrated cobalt nitrate (Co(NO3)2·6H2O) were used as raw materials to synthesize FBC / CoMoO4 composite materials by hydrothermal method, and finally sodium hypophosphite monohydrate was used as phosphorus source to prepare FBC / CoMoP composite materials by gas phase phosphating method. The prepared FBC / CoMoP composite materials were melt-compounded with sublimated sulfur powder to obtain the positive electrode material of lithium-sulfur battery.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] The present invention first discloses a method for preparing a biomass-derived carbon / bimetallic phosphide, comprising the following steps:

[0009] (1) Weigh 5-10 g of the middle layer of Ficus pumila and add it to anhydrous ethanol for washing, dry it, add 20-40 g of KOH and 400-800 mL of deionized water and stir evenly, leave it for 24 hours, filter the alkali solution, and obtain the pretreated middle layer of Ficus pumila;

[0010] (2) drying the pretreated Ficus pumila intermediate layer, heating it in a tube furnace for carbonization at a heating rate of 5°C / min to 600, 700 and 800°C, calcining it for 2 hours, taking it out, grinding it evenly in a mortar, washing it with deionized water in a centrifuge, and freeze-drying it for 12 hours after the measured pH was neutral to obtain FBC;

[0011] (3) Weigh a certain proportion of FBC and H 24 Mo7N6O 24 ·4H2O and Co(NO3)2·6H2O were added to a mixed solution of ethanol and deionized water and ultrasonically treated for 30 min and stirred for 1 h; FBC was 80-160 mg, H 24 Mo7N6O 24 The molar ratio of 4H2O and Co(NO3)2·6H2O is 1:1, and the volume ratio of ethanol and deionized water is 1:1 to obtain a mixed aqueous solution;

[0012] (4) After the mixed aqueous solution is stirred evenly, it is placed in a reaction kettle, sealed, and placed in an oven at 180° C. for reaction for 12 hours to obtain a FBC / CoMoO4 composite material;

[0013] (5) Weighing FBC / CoMoO4 composite material and sodium hypophosphite monohydrate in a mass ratio of 1:20, and subjecting them to high-temperature phosphating treatment in a tubular furnace at a heating rate of 5°C / min, heating to 800°C, and phosphating time of 2h to obtain FBC / CoMoP, i.e., biomass-derived carbon / bimetallic phosphide.

[0014] The invention also discloses a biomass-derived carbon / bimetallic phosphide prepared according to the preparation method.

[0015] The present invention also discloses an application of the biomass-derived carbon / bimetallic phosphide in preparing a positive electrode of a lithium-sulfur battery.

[0016] Furthermore, the application includes:

[0017] (1) Sublimed sulfur and FBC / CoMoP composite materials are uniformly mixed in a certain proportion, and FBC / CoMoP / S composite cathode materials are obtained by melt-injection sulfur filling in a vacuum or inert gas atmosphere; the mass proportion of biomass-derived carbon / bimetallic phosphide FBC / CoMoP in the FBC / CoMoP / S composite cathode materials is 20% to 30%; the melt-injection sulfur filling temperature is 155° C., and the time is 12 to 16 hours;

[0018] (2) The FBC / CoMoP / S composite positive electrode material, the conductive agent, and the binder are mixed in a mass ratio of 8:1:1 or 7:2:1, and nitrogen methyl pyrrolidone (NMP) is used as a solvent. The slurry is evenly coated on the current collector, and the positive electrode sheet of the lithium-sulfur battery is obtained after vacuum drying.

[0019] (3) Assembling the lithium-sulfur battery positive electrode, lithium negative electrode, separator, electrolyte and battery shell obtained in step (2) into a lithium-sulfur battery for electrochemical testing.

[0020] Furthermore, in step (2), the conductive agent is one or more of conductive carbon black, conductive graphite, carbon nanotubes, and graphene, and the binder is polyvinylidene fluoride.

[0021] Furthermore, the mixing method for uniformly mixing to form a slurry in step (2) is ball milling, the ball milling time is 1 to 2 hours, and the sulfur loading of the positive electrode sheet of the lithium-sulfur battery is 1 to 5 mg / cm 2 ; The positive electrode current collector used is carbon-coated aluminum foil.

[0022] The beneficial effects of the present invention are:

[0023] The present invention provides a method for preparing a biomass-derived carbon / bimetallic phosphide material, wherein a porous carbon material is obtained by a potassium hydroxide alkalization method and a high-temperature carbonization method, and then a hydrothermal method and a gas phase phosphating method are used to perform high-temperature phosphating in an inert gas environment to obtain a FBC / CoMoP composite material.

[0024] The biomass carbon material prepared by the present invention has good electrical conductivity, large specific surface area and pore structure, which can accelerate the ion transfer rate and improve the utilization rate of sulfur to the greatest extent. At the same time, the introduction of a transition bimetallic phosphide catalyst with high catalytic activity can increase the catalytic active sites in the FBC / CoMoP composite material and enhance the adsorption capacity of the FBC / CoMoP positive electrode material for polysulfides, thereby improving the redox kinetics of polysulfides during the electrochemical reaction, alleviating the shuttle effect of polysulfides, and reducing battery polarization. Experimental results show that when the FBC / CoMoP composite material is applied to the positive electrode material of a lithium-sulfur battery, the charge and discharge capacity, rate performance and cycle performance of the lithium-sulfur battery can be significantly improved. The preparation method of the present invention has mild reaction conditions and a simple process, which can provide a guiding idea for the commercial application of high-performance lithium-sulfur batteries in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A scanning electron microscope (SEM) image of the FBC / CoMoP material prepared in Example 1;

[0026] Figure 2A nitrogen isothermal adsorption / desorption curve diagram of the FBC material prepared in Example 2;

[0027] Figure 3 This is a comparison chart of the cycle performance at 0.5C when used in lithium-sulfur batteries. DETAILED DESCRIPTION

[0028] The present invention is described in detail below in conjunction with specific embodiments.

[0029] Embodiment 1:

[0030] A method for preparing biomass-derived carbon / bimetallic phosphide

[0031] (1) Weigh 5 g of the middle layer of P. Ficus microcarpa, add anhydrous ethanol to wash, dry, add 20 g of KOH and 400 mL of deionized water, soak and leave for 24 h;

[0032] (2) drying the Ficus pumila intermediate layer in step (1) at 110° C., carbonizing it in a tube furnace at 600° C. for 2 h, with a heating rate of 5° C. / min. After calcination, taking it out and grinding it evenly in a mortar, washing it with deionized water and centrifuging it in a centrifuge for 3 times, and after measuring the pH value of 7, freeze-drying it for 12 h to obtain FBC;

[0033] (3) Weigh 80 mg FBC, 0.72 g H 24 Mo7N6O 24 ·4H2O and 0.12g Co(NO3)2·6H2O were added to a mixed solution of 20mL ethanol and 20mL deionized water, ultrasonically homogenized for 30min and stirred for 1h;

[0034] (4) The aqueous solution of step (3) was stirred evenly and then placed in a reaction kettle, sealed, and placed in an oven at 180° C. for reaction for 12 h to obtain a FBC / CoMoO4 composite material;

[0035] (5) Weigh FBC / CoMoO4 powder and sodium hypophosphite monohydrate (mass ratio is 1:20) respectively. Place FBC / CoMoO4 purple precursor in the downstream area of ​​the quartz tube, and place sodium hypophosphite monohydrate on the upstream side of the tube furnace. Phosphate at 750℃ in the tube furnace for 2h, with a heating rate of 5℃ / min. After calcination, take out and grind evenly in a mortar to obtain FBC / CoMoP.

[0036] Embodiment 2:

[0037] A method for preparing biomass-derived carbon / bimetallic phosphide

[0038] (1) Weigh 5 g of the middle layer of P. Ficus microcarpa, add anhydrous ethanol to wash, dry, add 20 g of KOH and 400 mL of deionized water, soak and leave for 24 h;

[0039] (2) drying the Ficus pumila intermediate layer in step (1) at 110° C., carbonizing it in a tube furnace at 700° C. for 2 h, with a heating rate of 5° C. / min. After calcination, taking it out and grinding it evenly in a mortar, washing it with deionized water and centrifuging it in a centrifuge for 3 times, and after measuring the pH value of 7, freeze-drying it for 12 h to obtain FBC;

[0040] (3) Weigh 80 mg FBC, 0.72 g H 24 Mo7N6O 24 ·4H2O and 0.12g Co(NO3)2·6H2O were added to a mixed solution of 20mL ethanol and 20mL deionized water, ultrasonically homogenized for 30min and stirred for 1h;

[0041] (4) The aqueous solution of step (3) was stirred evenly and then placed in a reaction kettle, sealed, and placed in an oven at 180° C. for reaction for 12 h to obtain a FBC / CoMoO4 composite material;

[0042] (5) Weigh FBC / CoMoO4 powder and sodium hypophosphite monohydrate (mass ratio is 1:20) respectively. Place FBC / CoMoO4 purple precursor in the downstream area of ​​the quartz tube, and place sodium hypophosphite monohydrate on the upstream side of the tube furnace. Phosphate at 750℃ in the tube furnace for 2h, with a heating rate of 5℃ / min. After calcination, take out and grind evenly in a mortar to obtain FBC / CoMoP.

[0043] Embodiment 3:

[0044] A method for preparing biomass-derived carbon / bimetallic phosphide

[0045] (1) Weigh 5 g of the middle layer of P. Ficus microcarpa, add anhydrous ethanol to wash, dry, add 20 g of KOH and 400 mL of deionized water, soak and leave for 24 h;

[0046] (2) drying the Ficus pumila intermediate layer in step (1) at 110° C., carbonizing it in a tube furnace at 800° C. for 2 h, with a heating rate of 5° C. / min. After calcination, taking it out and grinding it evenly in a mortar, washing it with deionized water and centrifuging it in a centrifuge for 3 times, and after measuring the pH value of 7, freeze-drying it for 12 h to obtain FBC;

[0047] (3) Weigh 80 mg FBC, 0.72 g H 24 Mo7N6O 24 ·4H2O and 0.12g Co(NO3)2·6H2O were added to a mixed solution of 20mL ethanol and 20mL deionized water, ultrasonically homogenized for 30min and stirred for 1h;

[0048] (4) The aqueous solution of step (3) was stirred evenly and then placed in a reaction kettle, sealed, and placed in an oven at 180° C. for reaction for 12 h to obtain a FBC / CoMoO4 composite material;

[0049] (5) Weigh FBC / CoMoO4 powder and sodium hypophosphite monohydrate (mass ratio is 1:20) respectively. Place FBC / CoMoO4 purple precursor in the downstream area of ​​the quartz tube, and place sodium hypophosphite monohydrate on the upstream side of the tube furnace. Phosphate at 750℃ in the tube furnace for 2h, with a heating rate of 5℃ / min. After calcination, take out and grind evenly in a mortar to obtain FBC / CoMoP.

[0050] Figure 1 This is a scanning electron microscope (SEM) image of the FBC / CoMoP material prepared in Example 1; CoMoP is a rod-like structure distributed on the surface of biomass-derived porous carbon, proving that the material was successfully synthesized.

[0051] Figure 2 Nitrogen isothermal adsorption / desorption curve and pore size distribution diagram of the FBC material prepared in Example 2; the carbonized FBC presents a type I adsorption / desorption isotherm. From the figure, when P / P0<0.1, it can be seen that the type I adsorption isotherm shows a steep upward trend, proving that a large number of micropores exist on the FBC. When P / P0>0.1, the desorption curve shows a slight hysteresis, proving the presence of mesopores. FBC has a high specific surface area of ​​1487.46m2 / g. It has two pore sizes: micropores and mesopores. It achieves uniform sulfur distribution, provides fast ion transport channels, and sufficient space to buffer volume changes.

[0052] Application Example 1

[0053] Application of a biomass-derived carbon / bimetallic phosphide in the preparation of lithium-sulfur battery positive electrode

[0054] (1) Sublimed sulfur and FBC / CoMoP composite materials are uniformly mixed in a certain proportion, and FBC / CoMoP / S composite cathode materials are obtained by melt sulfur infusion under vacuum or inert gas atmosphere; the mass proportion of biomass-derived carbon / bimetallic phosphide FBC / CoMoP in the FBC / CoMoP / S composite cathode materials is 30%; the melt sulfur infusion temperature is 155°C and the time is 12h;

[0055] (2) The FBC / CoMoP / S composite positive electrode material, the conductive agent, and the binder are mixed in a mass ratio of 7:2:1, and nitrogen methyl pyrrolidone (NMP) is used as a solvent. The slurry is evenly coated on the current collector, and the positive electrode sheet of the lithium-sulfur battery is obtained after vacuum drying.

[0056] (3) Assembling the lithium-sulfur battery positive electrode, lithium negative electrode, separator, electrolyte and battery shell obtained in step (2) into a lithium-sulfur battery for electrochemical testing.

[0057] Furthermore, in step (2), the conductive agent is conductive carbon black, and the binder is polyvinylidene fluoride.

[0058] Furthermore, the mixing method for uniformly mixing to form a slurry in step (2) is ball milling, the ball milling time is 1 hour, and the sulfur loading of the positive electrode sheet of the lithium-sulfur battery is 1.2 mg / cm 2 ; The positive electrode current collector used is carbon-coated aluminum foil.

[0059] Figure 3 This is a comparison chart of the cycle performance of application example 1 in a lithium-sulfur battery at 0.5C; the discharge capacity of FBC / CoMoP / S as the positive electrode of a lithium-sulfur battery after 300 cycles is 847mAh / g, and the capacity retention rate is 88%. This shows that the FBC / CoMoP / S composite material can effectively improve the electrochemical reaction kinetics, inhibit the shuttle effect of polysulfides, and enhance battery stability.

Claims

1. A method for preparing a biomass-derived carbon / bimetallic phosphide, comprising: (1) soaking the Ficus pumila middle layer in anhydrous ethanol, drying it in an oven, taking the dried Ficus pumila middle layer, potassium hydroxide and deionized water and stirring them evenly, leaving them at room temperature for a period of time, filtering the alkali solution, and obtaining the pretreated Ficus pumila middle layer; (2) drying the pretreated Ficus pumila middle layer, heating and carbonizing it in a tube furnace, taking it out after calcination, grinding it evenly in a mortar, washing it with deionized water in a centrifuge, and freeze-drying it after the measured pH is neutral to obtain FBC; (3) adding FBC, ammonium molybdate tetrahydrate and cobalt nitrate hexahydrate to a mixed solution of ethanol and deionized water, ultrasonically homogenizing and magnetically stirring to obtain a mixed aqueous solution; (4) After the mixed aqueous solution is stirred evenly, it is placed in a reaction kettle and sealed, placed in an oven for reaction for several hours, cooled naturally, washed alternately with deionized water and anhydrous ethanol, and vacuum dried to obtain a FBC / CoMoO4 composite material; (5) Take FBC / CoMoO4 composite material and sodium hypophosphite monohydrate, place the FBC / CoMoO4 composite material in the downstream area of ​​the quartz tube, and place sodium hypophosphite monohydrate on the upstream side of the tube furnace, and perform high-temperature phosphating treatment by heating to obtain FBC / CoMoP, that is, biomass-derived carbon / bimetallic phosphide.

2. The preparation method according to claim 1, wherein: Step (1) The Ficus pumila intermediate layer is 5-10 g; KOH is 20-40 g; and deionized water is 400-800 mL; The stirring time of the Ficus pumila intermediate layer and the potassium hydroxide aqueous solution is 10 minutes, and the standing time at room temperature is 24 hours.

3. The preparation method according to claim 1, wherein: The heating rate of carbonization in step (2) is 5°C / min, the temperature is respectively raised to 600°C, 700°C and 800°C, the carbonization time is 2h, and the freeze-drying time is 12h.

4. The preparation method according to claim 1, wherein: In step (3), the molar ratio of FBC, ammonium molybdate tetrahydrate and cobalt nitrate hexahydrate is 1:1:1, and the volume ratio of ethanol to deionized water is 1:1; The ultrasonic time is 30 minutes, and the magnetic stirring time is 1 hour.

5. The preparation method according to claim 1, wherein: The oven reaction time in step (4) is 12 hours, the deionized water and anhydrous ethanol are alternately cleaned 3 to 6 times, the vacuum drying temperature is 60° C., and the drying time is 12 hours.

6. The preparation method according to claim 1, wherein: The mass ratio of the FBC / CoMoO4 composite material to sodium hypophosphite monohydrate in step (5) is 1:20; The high-temperature phosphating temperature is 750° C., the heating rate is 5° C. / min, and the phosphating time is 2 h.

7. A biomass-derived carbon / bimetallic phosphide prepared according to the preparation method of any one of claims 1 to 6.

8. Use of the biomass-derived carbon / bimetallic phosphide according to claim 7 in the preparation of positive electrodes for lithium-sulfur batteries.

9. The use according to claim 8, comprising: (1) uniformly mixing sublimated sulfur and biomass-derived carbon / bimetallic phosphide in a certain proportion, and obtaining a FBC / CoMoP / S composite cathode material by melt-filling sulfur under vacuum or inert gas atmosphere, wherein the heating temperature is 155° C. and the holding time is 12 to 16 hours; (2) mixing the FBC / CoMoP / S composite positive electrode material, the conductive agent, and the binder in a certain proportion, using nitrogen methyl pyrrolidone as a solvent, mixing them evenly to form a slurry, and then coating the slurry evenly on the current collector, and vacuum drying to obtain a positive electrode sheet for a lithium-sulfur battery; (3) Assembling the lithium-sulfur battery positive electrode, lithium negative electrode, separator, electrolyte and battery shell obtained in step (2) to obtain a lithium-sulfur battery.

10. The use according to claim 9, wherein: The mass proportion of biomass-derived carbon / bimetallic phosphide in the FBC / CoMoP / S composite cathode material in step (1) is 20% to 30%; In step (2), the mass ratio of the FBC / CoMoP / S composite positive electrode material, the conductive agent and the binder is 8:1:1 or 7:2:1.

Citation Information

Patent Citations

  • Metal phosphide and heteroatom doped porous carbon composite material as well as preparation and application thereof

    CN111434607A

  • Preparation method and application of hollow tube biomass carbon / nickel phosphide / sulfur composite material

    CN114464781A

  • Flexible inorganic composite nanofiber membrane photocatalyst as well as preparation method and application thereof

    CN115245835A

  • Lithium-sulfur battery positive electrode material as well as preparation method and application thereof

    CN116525800A